Uniform cooling of photovoltaic panels: A review. (May 2016) - Bahaidarah, Haitham M.S.; Baloch, Ahmer A.B.; Gandhidasan, Palanichamy
Abstract: Cooling of PV panels is a critical issue in the design and operation of concentrated photovoltaic (CPV) technology. Due to high cell temperature and non-uniform temperature distribution, current mismatching problem and hot spot occurs on the cell resulting in either reduction of efficiency or permanent structural damage due to thermal stresses. Temperature non-uniformity on the surface of PV panel has a major impact on the performance of CPV systems and directly increases cell temperature and series resistance. This review paper highlights the importance of uniform PV cooling by exploring the possible causes and effects of non-uniformity. Cooling techniques with low average cell temperature and uniform temperature distribution are analyzed. Economic and environmental impact on the importance of cooling of PV systems are discussed and an experimental case study is presented for comparison between uniform and non-uniform cooling methods. Immersion cooling is a promising solution for uniform cooling and has been reported to reduce the cell temperature to 20–45 °C for CPV systems. Heat pipes reduced the temperature down to 32 °C with the best case temperature non-uniformity of 3 °C. Passive cooling by heat sinks was found to reduce the cell temperature as low as 37 °C for high concentrations but with an expense of large heat sink area. Active cooling by microchannels, impingement cooling and hybrid microchannel-impingement cooling were found to be most effective in dissipating high heat flux from PV surface. Cell temperature was reported to decrease to 30 °C for 200× CPV using impingement cooling. For hybrid cooling, deviation of 0.46 °C surface temperature was obtained. Using PCM materials temperature of panel was controlled within 28–65 °C whereas optimization of heat exchanger designs also showed low and uniform temperature across surface. The impact of non-uniformity was found to be significant for all PV systems however the effect is more pronounced in CPV systems.